Locating naval bases and military infrastructure development in the Philippines - Mundo, Proscoro Ervin A.
The pull-out of the United States Armed Forces from all its military bases in the Philippines in 1991 led to the realization by the Armed Forces Philippines (AFP) of the security vacuum needed to defend Philippine national interest. In addition, the effects of the BCDA Law in 1992 forced the AFP to look for locations to construct new military bases outside of Manila. Moreover, issues affecting the AFP Modernization Program; the territorial issues in the West Philippine Sea; the protection of the vast offshore resources in Benham Rise; the increasing cross-border maritime piracy in Southern Philippine waters; the protection of Filipino maritime interest in the vast Exclusive Economic Zone of the country; and the globalization of maritime traffic transiting within the territorial waters necessitate the need to revisit the locations of military bases and plan out for the establishment of new military facilities in response to the dynamic security and defense policies of the country. The research covered an in-depth historical analysis to determine the patterns and factors that influence the site location of military bases across the centuries, which paved the way for the examination of the potential locations in establishing naval bases in the Philippines in the present time. The historical analysis revealed that during the Spanish colonial period, the military forts and the lighthouse dotting the coastal communities represented the colonizers' desire to control food supply and sea trade through military presence along maritime choke points and sea lines of communications. During the American colonial period toward the AFP Modernization (1898-1995), the selections of the geographical locations for the establishment of military facilities were based on multiple factors such as : a. Advancement of military technology available during the period e.g. airplane and radars; b. Internal and external security threats present during the site selection process e.g. Second World War, Cold War and insurgency (internal security; c. Socio-economic-political conditions e.g. 1986 EDSA Revolution, 1991 pull-out of US Bases and the 1997 financial crisis; and d. Policy imprimatur as an offshoot of an enactment of a specific (special) law affecting military planning e.g. National Defense Act of 1936, BCDA Law of 1992 and AFP Modernization Act of 1995. The research identified 371 bays, coves and harbors that meet the initial selection criteria for an area located along the sea and generally protected from typhoon and weather disturbances. The 371 locations were than analyzed based on Christaller's Central Place Theory (i.e. centrality of places and hierarchy of services) and the Weber-Moses Model of Industrial Location Theory (i.e. Least-cost; Market area; and Profit maximizing approach). The scalogram ranking and centrality index estimation were conducted at the regional level (e.g. sea board region in response to maritime area of interest) using 36 locational factors (parameters) generated through historical analysis and socio-economic-political analysis during the present time, indicated that there are less than twenty (20) locations in the country with near complete presence of factors (i.e. high centrality) and less than thirty (30) locations with about half of the factors present. Over 300 locations have five (5) factors or less and 26 locations with one (1) or zero(0) factor. The twp(2) most common factors are the SLOCs and Maritime Trade Routes and the two (2) least common factors are location near airport and commercial logistics facility. The areas with higher centrality were subjected to further analysis with the use of the multi-attribute utility theory (MAUT) and the iterative Delphi Technique to analyze the proposed hierarchy of bases and level of services at the national level and as follows; a. Main Naval Base to be located in Mactan-Cebu; b. Naval Operating Bases in Subic Bay, Ulugan Bay, and Margosatubig bay; c. Forward Operating Bases across the country: four (4) sites in Northern Luzon; one (1) in Southern Luzon; three (3) in Palawan; two (2) in Eastern Mindanao and two (2) in Southern Mindanao; d. Fleet-marine Training Bases on four (4) locations in Luzon and one (1) each for Visayas and Mindanao; and e. Naval Support Facilities to be primarily constructed in major urban areas to serve as administrative support facilities and primary housing areas. This research recommend the location and subsequent development of naval bases that are consistent with the country's regional development strategy and responsive to the country's national security requirements.